COMMUNICATION PATTERN BETWEEN PARENTS AND CHILDREN TIKTOK SOCIAL MEDIA USERS - Ridhatullah Assya’bani; Husin; Muhammad Azis; Abdul Rashid bin Abdul Aziz (International Forum of Researchers and Lecturers, 2022)
Communication patterns are very influential in maintaining relationships with the environment such as friends and family. One of the challenges in establishing effective communication patterns for children is social media. The Tiktok application is one of the social media that is now favored by many people, including children. This study aims to analyze the communication patterns between parents and teenagers using social media tiktok. This study uses Mary Anne Fitzpatrick's theory which reveals that family communication patterns depend on two important types of orientation, namely conversation orientation and conformity orientation.This study took place in Puyun village, Halong sub-district, Balangan district and was conducted by 10 informants, namely 5 children of tiktok users and 5 parents of children who use tiktok. The results of the study show that 1) one family of TikTok users has a communication pattern with a high conversational orientation and a high sense of compliance. 2) one family of children using tiktok has a communication pattern with low conversation orientation and high sense of compliance. 3) Three families of children who use tiktok have communication patterns with low conversation orientation and low sense of compliance.